CELL HEALTH LEARNING BASED ON DZIKRULLOH SPIRITUAL PRACTICE œHE NING CIPTO METAPHYSICS MEDITATION, TO BUILD A STRONG BODY IMMUNITY SYSTEM - Ahmad Qosyim; Erman Erman; Laily Rosdiana; Enny Susiyawati (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
This study aimed to describe the implementation of the Spiritual Practice-Based Learning Approach to Metaphysics Meditation